Prospects for the Development of Protective Structures in Poland Compared to the Experience of Some Other Countries - Skrabacz, Aleksandra; Gajewska, Paulina; Szewczyk, Irena (Roczniki Nauk Społecznych, 2025)
Protective buildings, as structures for both collective and individual protection of civilians, are one of the most effective ways of ensuring safety in situations of military and non-military threats. The total disintegration of the system of civil protection and civil defence in Poland, and with it the devastation of existing shelters and hiding places, as well as the lack of new investments, has resulted in less than 4% of the population in Poland being provided with protective structures. Meanwhile, global solutions in this area indicate that investing in protective structures is an investment in the safety of the civilian population. The article analyses solutions to this issue in countries such as Switzerland, Israel and Ukraine, in order to provide relevant recommendations for Poland.